2011
DOI: 10.1007/s10815-011-9550-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of micronuclei in lymphocytes of infertile males after exposure to gamma irradiation: a possible sign of genomic instability

Abstract: Purpose Induced chromosomal instability and micronucleus (MN) formation in blood lymphocytes of infertile men in comparison with fertile men exposed to gamma radiation was investigated. Methods Blood samples of healthy and infertile donors were irradiated by 2 and 4 Gy Co-60 gamma-rays, then cultured in RPMI-1640 complete medium containing 1% phytoheamaglutinin (PHA) and incubated in a CO 2 incubator. Cytochalasin-B was added to the cultures at a final concentration of 4 μg/ml. Finally, harvesting, slide makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Hoeller et al showed that individual radiosensitivity measured by lymphocytes might be a good way to predict fibrosis in breast cancer patients after radiotherapy ( 24 ). In the field of radiobiology, the CBMN Cyt assay for PBL is a suitable bio-dosimetry device to measure in-vivo and in-vitro radiosensitivity and cancer reproducibility ( 25 ). Lymphocytes are chosen because of their easy availability, simple method of culture, and ease of sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Hoeller et al showed that individual radiosensitivity measured by lymphocytes might be a good way to predict fibrosis in breast cancer patients after radiotherapy ( 24 ). In the field of radiobiology, the CBMN Cyt assay for PBL is a suitable bio-dosimetry device to measure in-vivo and in-vitro radiosensitivity and cancer reproducibility ( 25 ). Lymphocytes are chosen because of their easy availability, simple method of culture, and ease of sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Although PHA is widely employed on researches aimed to investigate molecular parameters in stimulation of lymphocytes, this mitogen is mainly effective in the stimulation and activation of T cells, acting differently for B lymphocytes that are negligibly stimulated (Vilasová et al 2008;Moghbeli-Nejad et al 2012). Henceforth, all results presented in this report are related to T lymphocytes (O'Donovan et al 1995).…”
Section: Discussionmentioning
confidence: 89%
“…In this research, lymphocytes were chosen due to the ease of obtaining and handling such cells in laboratory and as a result of the well-established method of labeling them with CFSE, especially for studies of immunology. Although PHA is widely employed on researches aimed to investigate molecular parameters in stimulation of lymphocytes, this mitogen is mainly effective in the stimulation and activation of T cells, acting differently for B lymphocytes that are negligibly stimulated (Vilasová et al 2008;Moghbeli-Nejad et al 2012). Henceforth, all results presented in this report are related to T lymphocytes (O'Donovan et al 1995).…”
Section: Discussionmentioning
confidence: 96%
“…This study carried on in three groups of oligospermic, azoospermic, and fertile men. They examined micronuclei frequency in blood samples of subjects when exposed to 0, 2 and 4 Gy of radiation ( 79 ). The results illustrated a statistically significant difference between the frequencies of micronuclei in lymphocytes of infertile individuals, compared to healthy donors, before and after exposure to gamma rays ( 79 ).…”
Section: Sperm Dna Damagementioning
confidence: 99%